Unveiling Resmetirom: A systematic review and meta‐analysis on its impact on liver function and safety in non‐alcoholic steatohepatitis treatment - Hashim Talib Hashim; Ahmed Qasim Mohammed Alhatemi; Sania Riaz; Mohammedbaqer Ali Al‐Ghuraibawi; Arwa S. Alabide; Humza Saeed; Fatimah Abdullah Sulaiman; Mustafa Ali Abd Alhussain; Maythum Ali Shallan; Ahmed Dheyaa Al‐Obaidi; Omar Saab; Hasan Al‐Obaidi; et al. (JGH Open)
Abstract Background and Aim The role of Resmetirom in non‐alcoholic steatohepatitis (NASH) represents a promising therapeutic approach in addressing the growing global burden of liver disease. With NASH emerging as a leading cause of liver‐related morbidity and mortality worldwide, there is an urgent need for effective treatments. Resmetirom, a selective thyroid hormone receptor‐β agonist, offers potential benefits in improving liver histology and metabolic parameters in patients with NASH. This review examines the current evidence surrounding Resmetirom's role in NASH management. Methods A systematic review and meta‐analysis was done by searching in Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, MEDLINE (including MEDLINE InProcess) (OvidSP), Web of Science, Embase (OvidSP), and Scopus databases. ROB2 Cochrane tool was used for assessing risk of bias in randomized controlled trials (RCTs). In the analysis, we used RevMan Cochrane software. Results The study showed that patients who were treated with Resmetirom had significantly lower low‐density lipoprotein‐cholesterol (LDL‐C) levels (mean difference [MD] −10.45; 95% confidence interval [CI] −15.86 to −5.83; P < 0.001) and alanine aminotransferase (ALT) levels (MD −7.18; 95% CI −12.67 to −1.68; P = 0.01) as compared with those in the placebo group. The risk of adverse events including diarrhea [risk ratio (RR) 1.81; 95% CI 1.40 to 2.35; P < 0.001] and nausea (RR 1.72; 95% CI 1.31 to 2.27; P < 0.001) was significantly increased for the Resmetirom group as compared with the placebo group. Conclusion Resmetirom presents a promising therapeutic option for NASH, offering potential benefits in reducing liver fat content and improving histological outcomes. The encouraging results from clinical trials suggest that Resmetirom may address an unmet need in NASH management, providing hope for patients with this progressive liver disease. Further research and long‐term studies are warranted to validate its efficacy and safety profile in larger patient populations.